Accessing the Safety Net: How Medicaid Affects Health and Recidivism - Analisa Packham; David Slusky (Institute of Labor Economics (IZA), 2023)
We estimate the causal impact of access to means-tested public health insurance coverage (Medicaid) on health outcomes and recidivism for those recently released from incarceration. To do so, we leverage a policy change in South Carolina that allowed simplified Medicaid re-enrollment for previously incarcerated eligible individuals. Using linked administrative data on criminal convictions and health insurance claims, we find that reducing barriers in access to Medicaid for vulnerable populations increases enrollment and utilization of health care services. However, we do not find that this improved health care insurance access reduces 1-year or 3-year recidivism, suggesting that effectiveness of such policies is context dependent.
Keywords: I38; I18; K42; 330; Medicaid; health care utilization; recidivism